What matters when examining the performance of salespersons? Analyzing the boundary conditions of personal dispositional factor - Muhammad Naeem; Muhammad Naeem; Fayaz Ali Shah; Shahid Jan Kakakhel; Shabana Gul (Frontiers in Psychology, 2022)
PurposeThis study intended to examine the effect of developmental and evaluative purposes of performance appraisal (PA) on job meaningfulness (JM). Furthermore, the study also aimed to assess the moderating effect of personal dispositional factors, that is, internal and external loci of control between developmental and evaluative PA and JM.Design/Methodology/ApproachA total of 295 questionnaires were received from salespersons working in national and multinational pharmaceutical companies in Khyber Pakhtunkhwa, Pakistan. Data were gathered using a time lag study design using a convenience sampling technique. Data collected via questionnaires were analyzed using PLS-SEM to assess measurement and structural models for testing hypotheses.FindingsResults revealed that developmental PA significantly influenced JM, while evaluative PA failed to influence JM. Furthermore, there was a moderating effect of the external locus of control (ELOC) on the relationship between developmental PA and JM, while the rest of moderating hypotheses failed to influence the relationship of developmental and evaluative PA with JM.Practical implicationsThe results can be used as a building block in order to bring positive work outcomes in the form of meaningful work. Organizations should use their PA as a development tool, instead of instrumental or evaluative PA, for making the work more meaningful to the employees.Originality/ValueThe extant literature is limited in terms of assessing the dimensions of PA (developmental and evaluative) in predicting workplace outcomes. Also, examinations of multidimensions of the locus of control are limited in the existing literature between HR practices and work outcomes. The current study has filled these gaps in the contemporary literature.